Genomic Characterization of Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus Implicated in Bloodstream Infections, KwaZulu-Natal, South Africa: A Pilot Study - Bakoena A. Hetsa; Jonathan Asante; Joshua Mbanga; Arshad Ismail; Akebe L. K. Abia; Daniel G. Amoako; Sabiha Y. Essack (MDPI AG, 2024)
Staphylococcus aureus is an opportunistic pathogen and a leading cause of bloodstream infections, with its capacity to acquire antibiotic resistance genes posing significant treatment challenges. This pilot study characterizes the genomic profiles of S. aureus isolates from patients with bloodstream infections in KwaZulu-Natal, South Africa, to gain insights into their resistance mechanisms, virulence factors, and clonal and phylogenetic relationships. Six multidrug-resistant (MDR) S. aureus isolates, comprising three methicillin-resistant S. aureus (MRSA) and three methicillin-susceptible S. aureus (MSSA), underwent whole genome sequencing and bioinformatics analysis. These isolates carried a range of resistance genes, including blaZ, aac(6')-aph(2"), ant(9)-Ia, ant(6)-Ia, and fosB. The mecA gene, which confers methicillin resistance, was detected only in MRSA strains. The isolates exhibited six distinct spa types (t9475, t355, t045, t1265, t1257, and t7888) and varied in virulence gene profiles. Panton-Valentine leukocidin (Luk-PV) was found in one MSSA isolate. Two SCCmec types, IVd(2B) and I(1B), were identified, and the isolates were classified into four multilocus sequence types (MLSTs), with ST5 (n = 3) being the most common. These sequence types clustered into two clonal complexes, CC5 and CC8. Notably, two MRSA clones were identified: ST5-CC5-t045-SCCmec_I(1B) and the human-associated endemic clone ST612-CC8-t1257-SCCmec_IVd(2B). Phylogenomic analysis revealed clustering by MLST, indicating strong genetic relationships within clonal complexes. These findings highlight the value of genomic surveillance in guiding targeted interventions to reduce treatment failures and mortality.